PENGGUNAAN PAYLATER DI KALANGAN MAHASISWA PERPAJAKAN - Jazila Yasmin; Venantya Asmandani; Boedijono Boedijono (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
The Covid-19 pandemic and new normal have caused changes in people's habits and mindsets. During the pandemic due to restrictions on activities outside the home, the use of e-commerce in Indonesia from 2020 to 2022 has increased. The paylater payment method has many enthusiasts from all circles of the general public, from students to business people. The type of research used in this study is qualitative descriptive research, with a sample of students of the DIII Taxation Study Program, Faculty of Social and Political Sciences, Jember University. The factors of interest of paylater users in making online shopping transactions are urgent needs, facilities offered, and ease of using paylater. While the factors of user interest not to use paylater are economic conditions, interest rates, knowledge of technological developments and the impact felt in the future